Persistent effect of ivermectin against Haemonchus contortus in goats. - Abdullah Sani, Rehana; Arshad, Siti Suri (Veterinary Association Malaysia, 1989)

(untitled)
A study on the efficacy of ivermectin in goats and its persistent effect against H. contortus is presented. Eighteen goats naturally infected with H. contortus were used in the study.Ten goats were given a single sc injection of ivermectin at a dose rate of 200 micro g/kg, while the remaining 8 goats acted as untreated controls. Faecal samples were taken 2 days prior to treatment and for several days after treatment for up to 33 days. The ova counts of treated goats were reduced to zero 24 h after treatment. This ova count remained zero until day 29 post- treatment when only one goat had H. contortus ova in its faeces. The other treated goats did not show evidence of worm burden up to 33 days post-treatment.